Hederagenin's uric acid-lowering effects in hyperuricemic mice: Mechanistic insights from molecular docking and in vivo analysis. - Ping Chen; Ya-Ni Tian; Jing-Tao Wang; Xiang-Lin Yin; Bao-Sheng Guan; Xue Bai (PLoS ONE, 2025)
This study explored the uric acid-lowering effects of hederagenin (HD) through molecular docking analysis and a chronic hyperuricemia (HUA) mouse model. Molecular docking was performed to evaluate HD's interactions key urate-regulating proteins, including xanthine oxidase (XOD), ABCG2, OAT1, URAT1, and GLUT9. To establish a chronic HUA model, mice were fed a yeast-adenine diet supplemented with potassium oxonate. The mice were randomly assigned to six groups: normal control, HUA model control, benzbromarone (BEN) group, and three HD treatment groups at doses of 50, 100, and 200 mg/kg. Serum uric acid (UA) levels, liver and kidney function indicators, XOD activity, and oxidative stress markers were assessed. Histopathological analyses of the liver and kidney were also conducted. In addition, gene and protein expression levels of urate transporters and inflammatory markers were assessed using RT-PCR and Western blotting. The results showed that HD interacts with XOD and urate transporters, significantly reducing serum UA levels and inhibiting XOD activity in HUA model. It also modulated the expression of urate transporter to enhance UA excretion. Moreover, HD protected liver and kidney function by reducing pro-inflammatory cytokine levels and inhibiting the TLR4/Myd88/NF-κB and NLRP3 signaling pathways. These findings suggest HD may serve as a promising therapeutic agent for lowing uric acid and preventing organ damage associated with HUA.